Implementing Rapid Application Development (RAD) for Statistical Analysis of Tourism and Travel Vlog Content - Singgalen, Yerik Afrianto (Journal of Information System Research (JOSH), 2024)
Technological developments have sparked creativity through innovation in tourism marketing strategies through various video content. There have not been many studies that use video statistical data as a reference to create other creative content and identify opportunities to increase viewers and subscribers to access a broader range of system users. This research offers ideas for designing Tourism and Travel Vlog Content Statistical Analysis using the Rapid Application Development (RAD) approach. The stages in the RAD method consist of the requirements planning stage, user design stage, construction stage, and cutover stage. This study's results show that user needs identification shows the need for Author Channel data, statistics, and relation patterns that can be used in Social Network Analysis (SNA). At the user design stage, the dashboard design creates a page where images or background videos are taken in content to SNA and Chain Network pages. In the construction stage, design is carried out according to the use case diagram to manage data and make data as helpful information in identifying publication opportunities so that the video rating made is by tourist preferences so that it can trigger intentions to visit tourist sites. At the cutover stage, testing the features and functions of the application is carried out; the test results show that all pages can be accessed without any problems. Thus, this application can analyze statistical data of content published on various platforms. This application generally benefits content creators who consider statistical information in addition to popular content design.